Comparing public attitudes towards providing for the livelihood of the elderly in two aging societies: Germany and Japan - Bernd Hayo; Hiroyuki Ono (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2007)
This paper studies attitudes about who should provide for the livelihood of the elderly in two aging societies, namely Germany and Japan. Applying an ordered logit model to individual data from representative public opinion surveys, it is analysed which socio-demographic, economic or political variables help to explain peoples attitudes on whether the government or individuals should be responsible for the livelihood of the elderly. We find that while higher income makes people more inclined towards the individual option, age is found to do the opposite in both countries. We conjecture that this age effect is related to the level of knowledge about the current situation of the public pension system. We also find that the part-time work status significantly affects attitudes in both countries, but not the same way. It affects adversely the inclination towards a government-based pension system in the case of Japan but positively in Germany. Other significant influences are the pensioner status of the respondents in Japan and their political position in the case of German data.
Keywords: H55; Z10; 330; Livelihood of elderly; pension reform; public attitudes; aging societies; Germany; Japan; Alterssicherung; Rentenfinanzierung; Meinung; Rentenreform; Alternde Bevölkerung; Deutschland; Japan